Ulul Albab Leadership and the Challenges of the Commodification of Education: A Philosophical Review - Salman Fathurohman; Riyan Nuryadin; Agi Kurniawan; Ridwan Awaludin (TA'DIB: Jurnal Pendidikan Agama Islam, 2025)
The phenomenon of the commodification of education has shifted the orientation of education from the formation of holistic human beings toward an economic instrument governed by market logic, efficiency, and profitability. This shift has contributed to a crisis of moral and intellectual leadership within educational institutions, where leaders tend to prioritize technocratic management over humanistic and ethical values. This article examines the commodification of education from a philosophical perspective and proposes the concept of Ulul Albab leadership as an alternative paradigm. Ulul Albab integrates three dimensions: dhikr (transcendental consciousness), fikr (critical rationality), and ‘amal (ethical–social responsibility), enabling educational leadership to be normative, reflective, and transformative in nature. This paradigm serves as an ethical critique of the dominance of market logic while simultaneously providing a philosophical framework for developing educational policies, organizational cultures, and practices that are inclusive, equitable, and oriented toward holistic human development. This study employs a qualitative approach based on a literature review of philosophical works and Islamic educational thought. The findings indicate that Ulul Albab leadership is not only normatively relevant but also carries practical implications for the management of contemporary educational institutions in the era of globalization and digitalization.